Strategi Komunikasi Personal Selling Merchandiser Display General Trade dalam Memenuhi Target Penjualan Di PT Kalbe Nutritional Cabang Bekasi: Studi Deskriptif Produk Diabetasol - Sari Nursyamsi; Nasaruddin Siregar; Diah Dwi Ratnasari (Brand Communication, 2022)
The research aims to see how personal communication is carried out by MD in approaching shop owners and what are the obstacles that occur during the approaching process at the GT outlet. So the writer can see firsthand how MD can get closer and provide understanding of the product well so that sales targets can be achieved. This type of research is qualitative with a descriptive approach and postpositivism paradigm which is an understanding of reality and interaction between researchers and what is studied. The results of this study indicate that personal selling communication conducted by MD runs well even though initially experiencing various obstacles. By finding out the characteristics of the shop owner, the introduction process, intense communication to the emergence of trust from the shop owner and so that the communication strategy can be right on target.